Thrombotic microangiopathy and systemic lupus erythematosus - María Laura Argüello Alegre; Cintia Verónica Marin; Marcelo De Rosa; Fernando Segovia (Revista de Nefrología, Diálisis y Trasplante, 2018)
A 28-year-old patient, a Jehovah's Witness, diagnosed with systemic lupus erythematosus with renal involvement four years earlier (class IV lupus nephritis with complete remission). After 2 and a half years, she reactivates renal involvement and adds during the re-induction phase hematological commitment with anemia and severe thrombocytopenia, schistocytes in peripheral blood smears, haptoglobin and decreased complement. The diagnosis of thrombotic microangiopathy (TMA) of primary versus secondary cause is proposed. For religious reasons MAT is treated with Rituximab, adding later Eculizumab. No pathological renal anatomy was performed, nor was plasmapheresis performed for this reason. It required dialytic treatment. ADAMTS XIII was normal and had significant C3 consumption. At 6 months of follow-up, without lupus activity, thrombocytopenia or hemolytic anemia, Rituximab and Eculizumab were discontinued. He continued on chronic dialysis treatment.